Beyond market failure: rationales for regional governmental venture capital. Issue 3 (3rd July 2021) - Vogelaar, Jan Jacob; Stam, Erik
ABSTRACT: Why do regional governments establish venture capital funds? Government intervention in venture capital markets is traditionally legitimised by market failure rationales. In this paper, we analyse the supply of public and private venture capital in Dutch regions, which reveals a multiplicity of rationales for government intervention in the regional economy. We ground this in the policy diffusion literature and distinguish four rationales for government intervention: economic competition, coercion, imitation and learning. The findings enrich the analysis of regional government interventions and challenge the rhetoric that regional policies seeking to foster venture capital markets are solely implemented to address market failures.